2003
DOI: 10.1016/s1044-0305(03)00067-9
|View full text |Cite
|
Sign up to set email alerts
|

Probing isomeric differences of phosphorylated carbohydrates through the use of ion/molecule reactions and FT-ICR MS

Abstract: Through the use of ion/molecule reactions and tandem mass spectrometry, phosphate position is assigned in both phosphorylated monosaccharides and oligosaccharides. In previous work [1, 2] phosphate moieties of monosaccharides were stabilized under collisional activation, by first derivatizing the deprotonated monosaccharide with trimethyl borate through an ion/molecule reaction, and the phosphate position determined through marker ions generated in tandem mass spectra. In this work, the methodology is extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 36 publications
(44 reference statements)
1
28
0
Order By: Relevance
“…The main challenge in sugar phosphate analysis by MS alone is that sugar phosphate isomers have the same m/z values and display similar MS-MS fragmentation patterns. [10] Therefore, in order to differentiate between sugar phosphate isomers, it would be necessary to introduce a separation step prior to their analysis by mass spectrometry. As mentioned earlier, CE is a particularly useful separation technique in this study, as it is suited to the separation of charged and polar molecules and has demonstrated the capability to separate regioisomers such as a-d-glucose-1-phosphate and d-glucose-6-phosphate on the basis of subtle differences in their pK a values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main challenge in sugar phosphate analysis by MS alone is that sugar phosphate isomers have the same m/z values and display similar MS-MS fragmentation patterns. [10] Therefore, in order to differentiate between sugar phosphate isomers, it would be necessary to introduce a separation step prior to their analysis by mass spectrometry. As mentioned earlier, CE is a particularly useful separation technique in this study, as it is suited to the separation of charged and polar molecules and has demonstrated the capability to separate regioisomers such as a-d-glucose-1-phosphate and d-glucose-6-phosphate on the basis of subtle differences in their pK a values.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Sugar phosphates are inherently polar compounds and possess a phosphate functional group, and the use of CE-ESMS in the negative mode would thus be a suitable choice of analy-A C H T U N G T R E N N U N G tical technique. [10,11] CE offers several advantages over other commonly used separation techniques, such as liquid chromatography (LC), in this context because it: 1) is particularly suited towards analyzing highly polar ionic molecules; 2) demonstrates better separation efficiency, which is ideal for resolving complex biological cell extracts and; 3) requires only small amounts of sample (in the low nL range). [12][13][14][15][16][17] In addition, the determination of the anomeric configurations of sugar phosphates by mass spectrometry can pose a challenge because regioisomers have identical m/z values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collision induced dissociation (CID), especially one carried out on an ion trap mass spectrometer (ITMS), is extremely important because it allows one to obtain detailed information of the precursor ion in focus through iterative ion‐molecule reactions at multiple CID stages (MS n ) 7–11. Some reports have described differences in the intensities and more recently energy‐resolved mass spectra (ERMS) of respective pairs of fragment ions from a pair of synthetic and naturally occurring oligosaccharides 12–18. However, such a comparison can only be made when a set of isomers is available.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, very little information existed for determining phosphorylation sites in carbohydrates because dissociation of underivatized phosphorylated oligosaccharides generates mainly phosphate cleavages [13]. Recently, we developed a method to determine the phosphate position of phosphorylated carbohydrates by using ion/molecule reactions and FT-ICR mass spectrometry [14,15]. Gas-phase reactions between phosphorylated hexose ions (HexXP, where X ϭ 1 or 6 indicating the linkage of the phosphate to the monosaccharide) and trimethyl borate (TMB) or trimethyl chloro-silane (TMSCl) result in distinguishable mass spectra.…”
mentioning
confidence: 99%